Undergraduate Biology Instructors Still Use Mostly Teacher-Centered Discourse Even When Teaching with Active Learning Strategies. (29th July 2020) - Kranzfelder, Petra; Bankers-Fulbright, Jennifer L; García-Ojeda, Marcos E; Melloy, Marin; Mohammed, Sagal; Warfa, Abdi-Rizak M
Abstract: Reform efforts in undergraduate science, technology, engineering, and mathematics (STEM) instruction often emphasize student-centered teaching approaches, but relatively little attention is paid to the way STEM teachers use discourse when interacting with their students. In the present study, we examined the instructional and discourse behaviors of biology faculty members (N = 20) teaching in undergraduate biology classes. Although we found that the biology teachers spent most of their time guiding student learning in active learning activities and less time presenting, an analysis of their classroom communicative approaches showed that the participants mostly used authoritative and not dialogic discourse to teach biology content. Similarly, we found a strong positive correlation between biology teachers guiding student learning and authoritative, interactive approaches, suggesting that these teachers mostly asked the students to recall facts or basic concepts rather than asking them to collaboratively build knowledge. We describe the implications of these findings and our results for undergraduate biology instruction.